Optimization and scale up of production of alkaline protease from Conidiobolus coronatus - Laxman, Ryali Seeta; Sonawane, A. P.; More, Shivaji V.; Rao, B. S.; Rele, M. V.; Jogdand, Vitthal V.; Deshpande, V. V.; Rao, M. B. (Process Biochemistry, 2005)
Alkaline protease secreted by Conidiobolus coronatus has been evaluated extensively in tanneries and finds application in pre-tanning operations in leather manufacture. It is important to produce the enzyme in inexpensive and optimized media on large scale for the process to be commercially viable. The present paper describes optimization of fermentation conditions in shake flasks and scale up of production to 100 L in fermentors. The production is complete in 2-3 days comparable to bacterial fermentations. The organism utilized several carbon sources such as starch, sucrose, lactose, glucose and fructose for production. Soyabean meal at an optimum concentration of 2-3% was found to be best inducer. Diammonium hydrogen phosphate, casamino acids and Hi-media peptone gave activities comparable to yeast extract. Preservation and stabilization studies showed that glycerol conferred considerable stabilization at room temperature while ammonium sulphate precipitated enzyme at 0.9 saturation was best with stability up to 2 years even at room temperature. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Alkaline Protease; Conidiobolus; Fermentation; Optimization; scale up

Oxidative dehydrogenation of ethylbenzene over vanadia-alumina catalysts in the presence of nitrous oxide: structure-activity relationship - Shiju, N. R.; Anilkumar, Mettu; Mirajkar, Subhash P.; Gopinath, Chinnakonda S.; Rao, B. S.; Satyanarayana, C. V. (Journal of Catalysis, 2005)
A series of vanadia-alumina catalysts with different vanadia contents were prepared by a wet impregnation method. The influence of the local structure of vanadia in these catalysts on the oxidative dehydrogenation of ethylbenzene with nitrous oxide was investigated. The use of N2O as a co-feed remarkably enhanced the styrene yield compared with the use of N-2. Characterization of these vanadia catalysts by XRD, FTIR, UV-vis, TPR, XPS, and V-51 NMR techniques suggests that the nature of the VOx species depends on the vanadia loading: the predominant species are monomeric vanadia at lower loadings, two-dimensional polyvanadates at intermediate loadings, and bulk-like V2O5 and AlVO4 at higher loadings. The rate of oxidative dehydrogenation (ODH) of ethylbenzene per vanadium atom increases with vanadia loading and reaches a maximum at 10 wt%, the loading at which the surface predominantly contains polyvanadate species. The observed variation in the selectivity of products with vanadium loading indicates that the monomeric V5+ species favors dehydrogenation, whereas bulk-like V2O5 preferentially participates in the dealkylation of ethylbenzene. The vanadium species remains at a higher oxidation state in the presence of N2O, leading to a higher styrene yield. than in a N-2 atmosphere. The ODH turnover rates increased with decreasing energy of the absorption edge in the UV-vis spectrum, at low VOx coverages of less than one monolayer on the Al2O3 surface. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: absorption edge energy; Alumina; ethylbenzene; Nitrous oxide; oxidative dehydrogenation; polyvanadates; styrene; vanadia